2015
DOI: 10.1039/c5dt02612a
|View full text |Cite
|
Sign up to set email alerts
|

Non-redox metal ions can promote Wacker-type oxidations even better than copper(ii): a new opportunity in catalyst design

Abstract: In Wacker oxidation and inspired Pd(ii)/Cu(ii)-catalyzed C-H activations, copper(ii) is believed to serve in re-oxidizing of Pd(0) in the catalytic cycle. Herein we report that non-redox metal ions like Sc(iii) can promote Wacker-type oxidations even better than Cu(ii); both Sc(iii) and Cu(ii) can greatly promote Pd(ii)-catalyzed olefin isomerization in which the redox properties of Cu(ii) are not essential, indicating that the Lewis acid properties of Cu(ii) can play a significant role in Pd(ii)-catalyzed C-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 72 publications
(1 reference statement)
14
47
0
Order By: Relevance
“…However, when the ratio continuously increased from 1 to 2, the efficiency improvement is relatively minor. This phenomenon is similar to those in allylbenzene isomerization, but distinctly different from that in Wacker-type oxidations catalyzed by Pd(OAc) 2 /Lewis acid [33][34][35]. In Wacker-type oxidation, the Sc(III)/Pd(II) ratio of 4 is much more efficient than the ratio of 1.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…However, when the ratio continuously increased from 1 to 2, the efficiency improvement is relatively minor. This phenomenon is similar to those in allylbenzene isomerization, but distinctly different from that in Wacker-type oxidations catalyzed by Pd(OAc) 2 /Lewis acid [33][34][35]. In Wacker-type oxidation, the Sc(III)/Pd(II) ratio of 4 is much more efficient than the ratio of 1.…”
Section: Resultssupporting
confidence: 50%
“…In previous studies, it has been observed by UV-Vis spectra that adding non-redox metal salts like Sc(OTf) 3 or Al(OTf) 3 to Pd(OAc) 2 in acetonitrile would generate the new Pd(II) species, and it was further evidenced by NMR studies [33][34][35]. Taken together with the facts that heterobimetallic Pd(II) dimers having an acetate bridge with bivalent or trivalent metal ions, including Ba 2+ , Sr 2+ , Ca 2+ , Mn 2+ , Co 2+ , Ni 2+ , Cd 2+ , Zn 2+ Ce 3+ , Nd 3+ , Eu 3+ and Ce 4+ , have been widely reported [45][46][47][48], we proposed the formation of the heterobimetallic Pd(II)/Sc(III) or Pd(II)/Al(III) dimer having an acetate bridge as the key species for Wacker-type oxidation, olefin isomerization and oxidative coupling reactions [33][34][35]. In the present studies, the UV-Vis kinetics of Pd(OAc) 2 /Sc(OTf) 3 in toluene/t-BuOH solvent also indicated the formation of the new Pd(II) species.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This phenomenon shed light on the mechanism because the manipulation of the catalytic properties always originated from the interaction of non‐redox metals with transition‐metal complexes through metal−oxo−metal or metal−H−metal bonds. This interaction has been observed in our previous studies and in the work of others . Thus, the presence of Ru−H in the RuH 2 (CO)(PPh 3 ) 3 /Mg 2+ system was essential to promote the isomerization from which it was speculated that the regulation of the non‐redox metals on the Ru center may originate from metal−H−metal bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The role of Mg 2+ was mainly: 1) to twist the first coordination sphere of the Ru center. This twisting, together with steric hindrance from OTf − anions, induced the dissociation of the PPh 3 ligand and the formation of an unoccupied coordination site for alkene and 2) to interact with the Ru center through hydride, because of which the strain associated with the Ru−H bond could be relieved by invoking a Mg‐bridged species that benefitted the isomerization of the alkene . This acceleration was similar to the case of the redox isomerization of propargyl alcohols, in which the interaction of In 3+ with Ru species through Ru−Cl−In 3+ also benefitted the isomerization process .…”
Section: Resultsmentioning
confidence: 99%